2020
DOI: 10.1111/gbi.12384
|View full text |Cite
|
Sign up to set email alerts
|

The impact of marine nutrient abundance on early eukaryotic ecosystems

Abstract: The rise of eukaryotes to ecological prominence represents one of the most dramatic shifts in the history of Earth's biosphere. However, there is an enigmatic temporal lag between the emergence of eukaryotic organisms in the fossil record and their much later ecological expansion. In parallel, there is evidence for a secular increase in the availability of the key macronutrient phosphorus (P) in Earth's oceans. Here, we use an Earth system model equipped with a size‐structured marine ecosystem to explore relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
85
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(91 citation statements)
references
References 99 publications
(183 reference statements)
5
85
1
Order By: Relevance
“…By 560 Ma, motile macroscopic bilaterians, which would have required more food and oxygen than their sessile ancestors (9), also began to diversify. A direct link between marine P concentration and ecosystem structure and size has also recently been found in an Earth system model (73), consistent with our hypothesis linking these ecosystem changes to increased remineralization of organic phosphorus via sulfate reduction.…”
Section: Discussionsupporting
confidence: 91%
“…By 560 Ma, motile macroscopic bilaterians, which would have required more food and oxygen than their sessile ancestors (9), also began to diversify. A direct link between marine P concentration and ecosystem structure and size has also recently been found in an Earth system model (73), consistent with our hypothesis linking these ecosystem changes to increased remineralization of organic phosphorus via sulfate reduction.…”
Section: Discussionsupporting
confidence: 91%
“…Of note, a recent review of animal ecology across natural gradients in food supply on abyssal plains demonstrated that increased food supply is associated with increases in diversity, animal biomass, sediment mixed‐layer depth, and specialist predator types (Sperling & Stockey, ). These are many of the same ecological changes that are seen across modern oxygen gradients in oxygen minimum zones (OMZs; Rhoads & Morse, ; Sperling, Frieder, et al, ; Sperling, Halverson, et al, ), which are often invoked as prima facie evidence that oxygen changes could have driven the Cambrian radiation (Reinhard et al, accepted).…”
Section: Point–counterpoint Argumentsmentioning
confidence: 94%
“…However, in recent years there has been an upswing in interest in modeling Proterozoic marine environments and a jump in the complexity of models being utilized. For instance, the intermediate‐complexity Earth system model cGENIE has been utilized by several groups to explore marine redox structure leading up to and during the rise and diversification of metazoans (Reinhard et al, ), and more recently to explore the potential impacts of marine nutrient levels on eukaryotic trophic ecology (Reinhard et al, accepted). As an alternative approach, estimates of marine physical dynamics at various climate states from higher resolution GCMs have been coupled with marine biogeochemical models (Bellefroid et al, ).…”
Section: Point–counterpoint Argumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, enhanced phosphorus (P) scavenging in the anoxic, iron rich Mesoproterozoic ocean may have reduced P availability (Derry, 2015; Reinhard et al, 2017; Zegeye et al, 2012). The scarcity of macronutrient elements (N or P, or both) could have limited the rate of primary productivity in the ocean, which, in turn, may have delayed eukaryotic evolution (Anbar & Knoll, 2002; Fennel et al, 2005; Reinhard et al, 2017, 2020).…”
Section: Introductionmentioning
confidence: 99%